The fecal microbiota of irritable bowel syndrome patients differs significantly from that of healthy subjects - Kassinen, Anna; Krogius-Kurikka, Lotta; Mäkivuokko, Harri; Rinttilä, Teemu; Paulin, Lars; Corander, Jukka; Malinen, Erja; Apajalahti, Juha; Palva, Airi (Gastroenterology (New York, N.Y. 1943), 2007)
Irritable bowel syndrome (IBS) is a significant gastrointestinal disorder with unknown etiology. The symptoms can greatly weaken patients' quality of life and account for notable economical costs for society. Contribution of the gastrointestinal microbiota in IBS has been suggested. Our objective was to characterize putative differences in gastrointestinal microbiota between patients with IBS and control subjects. These differences could potentially have a causal relationship with the syndrome. Microbial genomes from fecal samples of 24 patients with IBS and 23 controls were collected, pooled in a groupwise manner, and fractionated according to their guanine cytosine content. Selected fractions were analyzed by extensive high-throughput 16S ribosomal RNA gene cloning and sequencing of 3753 clones. Some of the revealed phylogenetic differences were further confirmed by quantitative polymerase chain reaction assays on individual samples. The coverage of the clone libraries of IBS subtypes and control subjects differed significantly (P < .0253). The samples were also distinguishable by the Bayesian analysis of bacterial population structure. Moreover, significant (P < .05) differences between the clone libraries were found in several bacterial genera, which could be verified by quantitative polymerase chain reaction assays of phylotypes belonging to the genera Coprococcus, Collinsella, and Coprobacillus. The study showed that fecal microbiota is significantly altered in IBS. Further studies on molecular mechanisms underlying these alterations are needed to elucidate the exact role of intestinal bacteria in IBS.